La solution de la question sociale. - Willaey, E (Paris : Albert Messein, 1912)
Bibliotheek E. Anseele
Dedicator: Willaey, E., dedicatee: Anseele, Edward (sr.)
Met autografische opdracht van de auteur aan E. Anseele
Frans
Brochure